O treinamento e a capacitação dos recursos humanos como determinantes de eficiência técnica das agências do Banco do Estado do Rio Grande do Sul - Fernandes, Leonardo da Silva (Universidade do Vale do Rio dos Sinos, 2021)
This study aims to analyze if the training and qualification of human resources accomplished by the Bank of the State of Rio Grande do Sul are determinants in the technical efficiency of the branches. To reach the objective of the research a case study was carried out with 393 agencies distributed in the state of Rio Grande do Sul. For this, the method used to verify the internal efficiency was Data Envelopment Analysis (DEA), and after, of a linear regression model to ascertain the external effect, finally, the DEA was re-estimated to analyze the pure technical efficiency. The study pointed out that hours of training and qualification are decisive in the technical efficiency of Banrisul's agencies. The external variables that most influence efficiency scores are agencies located in Porto Alegre, population and economic activity related to agribusiness, with the profile of the agencies and, consequently, with the analysis of internal efficiency. By the temporal analysis, it was found that the external environment causes a different influence in determining efficiency. The study also identified that the variable hours of training and qualification is the input that most influences the increase in the score of pure technical efficiency of the agencies, although not not being able to explain it in isolation. It´s suggested that training and qualification be used in conjunction with other actions relevant to Human Resources Management in order to obtain higher levels of organizational performance.
Keywords: Treinamento; Eficiência técnica; Desempenho; Recursos humanos; Banrisul; Training; Technical efficiency; Performance; Human resources; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis